Framework for land value capture from investments in transit in car-dependent cities - McIntosh, James Robert; Newman, Peter; Trubka, Roman; Kenworthy, Jeff (Journal of Transport and Land Use, 2015)
Many car-dependent cities have major transit projects stuck in financial and economic assessment due to inadequate links between land use, transport, and funding. This has left most urban transport networks underfunded and requiring significant government support. During this widening transit funding gap, there has been an international increase in demand on transit systems, which is in part a response to the global peak in car use per capita. This paper demonstrates to transit proponents and practitioners how to facilitate infrastructure projects by optimizing induced and activated land-use change. A five-step framework for assessment is proposed that includes assessing the regional and local legislation and regulations to determine what alternative funding opportunities are available, undertaking accessibility beneficiary analysis, analyzing the project-induced land value uplift, developing an alternative funding strategy to implement integrated land-use and transport planning mechanisms, and preparing a procurement and delivery strategy. The proposed assessment framework enables transit business cases to extend project funding for integrated transit and land-use projects, especially in car-dependent cities. This is demonstrated through a case study of Perth, Western Australia.